Foucault and human capital as hegemonic strategy. Reflections for a critique of the educational-formative dimension of neoliberalism. (2024)
Objective: The article presents theoretical results of the research project "Experience, ethics and subject in the last Foucault", which conceptualized the theoretical-methodological categories of the philosopher's last period of work; the text presents the educational dimension of contemporary neoliberalism located in human capital as discourse and practice that produces scenarios of formation and constitution of subjectivities oriented by the policies of international order and the practices in the educational institutions of basic secondary and higher education. Originality/support: It is circumscribed to the studies consolidated in recent times as philosophy of education, in the sense of using concepts and categories of philosophy to problematize and study with effects produced by policies and forms of economy in the field of educational sciences and pedagogy. Method: The methodology is close to Michel Foucault's archeological-genealogical-ethical approach, materialized in different instruments such as thematic and analytical cards that allow us to recognize the statements and conceptual series that reorganize the way the educational forms of neoliberalism have been constituted and the effects on contemporary subjects and institutions; apart from the procedure, the essay-problematization is used not as a simple description of the constructed situation, but with the intention and conviction of the transformation of the research subject; that is, not to record the social practices produced in the discourses, but the ways in which the subject becomes restless and generates different possibilities of action. Strategies/information collection: The article resorts to theoretical and documentary sources from philosophy and economics, privileging Foucault's courses taught at the Collège de France during the years 1977-1979, while dwelling on the analyses of North American neoliberals (Schultz, Becker), theorists of human capital, who postulate the economic value of education. Conclusions: Contemporary education in Colombia and Latin America is co-opted by neoliberalism as a world vision. This verification is materialized in human capital as a formative scene that includes turning students and teachers to the competency model and its materialization in curricula and institutional adventures such as innovation, entrepreneurship and the management of subjects as forgers of their own destiny, being entrepreneurs of themselves to offer themselves in the different labor markets.